THE PROBLEM OF THE BREST UNION IN HISTORICAL LITERATURE OF XIX AND XX CENTURIES - R. Shved (Academy of Cognitive and Natural Sciences, 2002)
The article shows the role of the Brest union in the formation of national consciousness o f the Ukrainian nobility and Cossacks.